MANAJEMEN MUTU UNTUK PENGEMBANGAN AGROWISATA BERBASIS MASYARAKAT - Pontoan, Karen Alfa; Lengkong, Meilany Rosita; Loho, Ambrosius Markus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Quality is an inherent characteristic of a product. In addition, quality is also a benchmark for a product to compete in the market. In the context of this research, the author aims to outline the main scope of quality within the big frame that oversees it, namely management. Therefore, quality management always needs to be seen in unity because the quality of a product needs to be organized and adjusted in order to compete in the market. Within the framework of this research, the author describes the application of quality management in the development of community-based agritourism. The quality of an agritourism as an agricultural-based tourist destination, must continue to be promoted and formed on an ongoing basis in order to compete in the global arena. Finally, the implementation of quality management must be closely related to the development of community-based agritourism. Because agritourism is a tourism service business that diversifies local agribusiness products, which also fosters employment opportunities and business opportunities for local communities. Keywords: